2015
DOI: 10.1016/j.nima.2014.11.085
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission and optical constant measurements of a Cesium Iodide thin film photocathode

Abstract: The performance of cesium iodide as a reflective photocathode is presented. The absolute quantum efficiency of a 500 nm thick film of cesium iodide has been measured in the wavelength range 150 nm to 200 nm. The optical absorbance has been analyzed in the wavelength range 190 nm to 900 nm and the optical band gap energy has been calculated. The dispersion properties were determined from the refractive index using an envelope plot of the transmittance data. The morphological and elemental film composition have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…The optical absorption of reflective and semitransparent CsI thin films has been obtained by C. Lu et al [16], P. Maier et al [37], T. Boutboul et al [38] and Triloki et al [15]. We found that our results are having good match with them.…”
Section: Optical Properties Of Csi Thin Filmssupporting
confidence: 85%
See 1 more Smart Citation
“…The optical absorption of reflective and semitransparent CsI thin films has been obtained by C. Lu et al [16], P. Maier et al [37], T. Boutboul et al [38] and Triloki et al [15]. We found that our results are having good match with them.…”
Section: Optical Properties Of Csi Thin Filmssupporting
confidence: 85%
“…Cesium Iodide (CsI) thin films are widely used as photoelectron converters in particle physics and medical imaging experiments [1,2] due to its high quantum efficiency (QE) in the ultraviolet (UV) spectral range [3][4][5][6], a high secondary electron emission (SEE) yield [7,8], a relatively high stability in air among other alkali halides material [9] and its capability to operate in a stable way with gaseous detectors [10,11]. In the recent past, a lot of research work has been done in order to enhance its QE [12][13][14] and several groups have made progress in this respect and a quantum efficiency of about 35-40% at 150-160 nm has been reported for a 500 nm CsI thin film [15,16]. Under humid-free gas atmosphere, CsI thin film has been coupled successfully with a multiwire proportional chamber (MWPC) and various micropattern gas detectors such as gas electron multiplier (GEM), thick gas electron multiplier (THGEM) [4,17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many materials are clearly not suitable: metals have too low a quantum yield even with surface modifi-cation, 8 while alkali halides, such as CsI with h z 40%, have high work function and are hence solar blind. 9 Conventional high-performance bialkali photocathodes can give work function approaching 1.5 eV and h as high as 40%. 10 Although these materials are normally used in vacuum and considered vulnerable to surface contamination, it has been demonstrated that K-Cs-Sb photocathodes can operate in atmospheric pressure gaseous photomultipliers with h = 10%-20% in the range 300-400 nm.…”
Section: Is Photoelectric Solar Power Feasible?mentioning
confidence: 99%